Quantitative food intake in the EPIC-Germany Cohorts - Schulze, Matthias Bernd; Brandstetter, Birgit; Wahrendorf, Jürgen (Annals of nutrition & metabolism, 1999)
The EPIC-Heidelberg and the EPIC-Potsdam studies with about 53,000 study participants represent the German contribution to the EPIC (European Investigation into Cancer and Nutrition) cohort study. Within the EPIC study, standardized 24-hour dietary recalls were applied as a quantitative calibration method in order to estimate the amount of scaling bias introduced by the varying center-specific dietary assessment methods. This article presents intake of food items and food groups in the two German cohorts estimated by 24-hour quantitative dietary recalls. Recalls from 1,013 men and 1,078 women in Heidelberg and 1,032 men and 898 women in Potsdam were included in the analysis. The intake of recorded food items or recipe ingredients as well as fat used for cooking was summarized into 16 main food groups and a variety of different subgroups stratified by sex and weighted for the day of the week and age. In more than 90% of the recalls, consumption of dairy products, cereals and cereal products, bread, fat, and non-alcoholic beverages, particularly coffee/tea, was reported. Inter-cohort evaluations revealed that bread, potatoes, fruit and fat were consumed in higher amounts in the Potsdam cohort while the opposite was found for pasta/rice, non-alcoholic, and alcoholic beverages. It was concluded that the exposure variation was increased by having two instead of one EPIC study centers in Germany.